Design of a Web-Based Petty Cash Accounting Information System at Otoritas Jasa Keuangan (OJK) Regional Office 2 of West Java - Rosita Apriyanti, Rosita Apriyanti; Perwito; Rini Suwartika (Politeknik Piksi Ganesha Indonesia, 2023)
The rapid development of technology makes it easy for a company to get information. One is at Otoritas Jasa Keuangan (OJK) Regional Office 2 of West Java. One of the problems found is in the process of processing accounting data which is still done manually using the Spreadsheet application, so a Web-Based Accounting Information System is designed, with the software development method used namely a waterfall with the Unified Modeling Language (UML) modeling system tools. While the PHP programming language and MySQL database. This research produces an information system integrated into recording cash and preparing company cash reports. This accounting information system's design allows petty cash records to be managed effectively and efficiently.